Associations of Magnesium Intake with Acyclic Pelvic Pain and Dysmenorrhea - Tadess, Beza (My University, 2023)
Background: Pelvic pain (with or without endometriosis) is responsible for the deterioration of quality of life, chronic absenteeism and truancy, and loss of intimate relationships. Magnesium is a mineral that aids in muscular relaxation and can relieve cramps in a variety of muscles, including those in the pelvic floor. Little is known about the role of diet, particularly magnesium intake, as a modifiable risk factor in chronic pelvic pain symptoms and dysmenorrhea among adolescents. We investigated associations of magnesium intake with dysmenorrhea and acyclic pelvic pain. We also examined potential modifiers of the associations. Methods: We conducted a cross-sectional analysis in the Women’s Health Study: Adolescence to Adulthood (A2A) participants. A2A is a longitudinal cohort study of women aged 7 -55 recruited from the Boston area. Our analytic population (N=938) comprised of participants with and without endometriosis aged 7-25 years. Exposure, average weekly magnesium intake (dietary and supplement) over the past year, was assessed based on responses to a self-reported food frequency questionnaire. Outcomes, acyclic pain and dysmenorrhea, were assessed using the Visual Analog Scale pain scale. We used unadjusted and adjusted logistic regression models to calculate odds ratios (ORs) and corresponding 95% confidence intervals (CI) relating the exposure (quartiles of average weekly intake of magnesium) with outcomes (mild/moderate Vs. severe pain). Adjusted models included a priori selected confounders including age at enrollment, age at menarche, body mass index (BMI), parity, physical activity, and race. All models included total caloric intake. We also examined the associations across subgroups defined by race (white vs. non-white) and endometriosis status (cases vs. non-cases) to explore potential differences in associations. Results: The median age of participants was 20 years (range 7 to 25 years). About 81% were white and 53% had been diagnosed with endometriosis. Two-thirds (66%) of participants self-reported severe acyclic pain and over half (55%) self-reported severe dysmenorrhea. Overall, we did not find significant associations of magnesium intake with acyclic pain or dysmenorrhea after adjustment for covariates (all p-trend>0.05). Our observations were similar when participants were stratified by endometriosis case status. In race-stratified analyses, we did not find associations of magnesium intake with acyclic pain among white participants. We were not able to assess association of magnesium intake with acyclic pain among non-whites due to small numbers. We found the suggestion of an association between magnesium intake and dysmenorrhea among non-white participants, but not among white participants. The adjusted odds ratios (adjORs) for participants in the second, third, and fourth quartiles of magnesium intake, compared with participants in the first quartile, were 1.04 (95% CI: 0.21-5.60), 1.22 (95% CI: 0.22-7.20), and 5.01 (95% CI: 0.90-32.4) (p-trend=0.07). Corresponding estimates among white participants were 1.04 (95% CI: 0.90-1.20), 0.99 (95% CI: 0.86-1.15), and 1.02 (95% CI: 0.87-1.20) (p-trend>0.90). The p-value for the interaction of magnesium intake with race on dysmenorrhea was not statistically significant (p-interaction>0.05). Conclusion: We found no significant association between magnesium intake and severe acyclic pain or severe dysmenorrhea overall or among participants with or without endometriosis. Our findings suggest a potential association between magnesium intake and dysmenorrhea that differed by racial groups. These findings suggest that magnesium intake may not be a major contributing factor in the severity of acyclic pain or dysmenorrhea. Further research with larger sample sizes is needed to confirm our observations and explore other potential factors influencing the associations. Keywords: dysmenorrhea, acyclic pelvic pain, endometriosis, magnesium
Thesis (Master's)--University of Washington, 2023
Keywords: Epidemiology; Epidemiology